2012
DOI: 10.1007/s00701-012-1565-0
|View full text |Cite
|
Sign up to set email alerts
|

Volume and densities of chronic subdural haematoma obtained from CT imaging as predictors of postoperative recurrence: a prospective study of 107 operated patients

Abstract: BackgroundChronic subdural haematoma (CSDH) is a common entity in neurosurgery with a considerable postoperative recurrence rate. Computerised tomography (CT) scanning remains the most important diagnostic test for this disorder. The aim of this study was to characterise the relationship between the recurrence of CSDH after treatment with burr-hole irrigation and closed-system drainage technique and CT scan features of these lesions to assess whether CT findings can be used to predict recurrence.MethodsWe inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 31 publications
(56 reference statements)
8
96
6
1
Order By: Relevance
“…With a postoperative thickness greater than 14 mm, the risk of a poor recovery was increased four-fold. Stanisic et al reported similar results concerning recovery and recurrence [28]. In our series, the homogeneity of the CSH on the preoperative CT scan, side, bilateral or unilateral, and surgical technique, were not associated with a significantly different functional outcome.…”
Section: Functional Outcomesupporting
confidence: 89%
See 2 more Smart Citations
“…With a postoperative thickness greater than 14 mm, the risk of a poor recovery was increased four-fold. Stanisic et al reported similar results concerning recovery and recurrence [28]. In our series, the homogeneity of the CSH on the preoperative CT scan, side, bilateral or unilateral, and surgical technique, were not associated with a significantly different functional outcome.…”
Section: Functional Outcomesupporting
confidence: 89%
“…In our study, CSH homogeneity on the preoperative CT scan was not associated with a lower rate of recurrence, in contradiction to other studies [8,28]. A radiographic classification has been described in the literature, in order to assess the evolution of the CSH [20].…”
Section: Recurrencecontrasting
confidence: 84%
See 1 more Smart Citation
“…Chronic SDH may recur in 6-24 % [38,43]. Recurrence is more likely to happen in patients with preoperative hematoma volume greater than 115 mL and postoperative residual hematoma volume greater than 80 mL, postoperative midline shift greater than 5 mm, preoperative seizures, and in patients on anticoagulant therapy [38,[44][45][46]. In addition, patients with diabetes mellitus, multilocular hematoma, and massive postoperative subdural air are at an increased risk of SDH recurrence.…”
Section: Prognosismentioning
confidence: 93%
“…The open variant should be chosen only if irrigation is desired: the dura and external membrane are opened widely so that the fluid of the hematoma and irrigation can drip out beside the drain during rinsing. Removal of the fluid enriched with inflammatory mediators is considered obviously as an advantage, although a remaining pneumocephalus is seen as an approved factor of recurrence [5,6]. Thus, we prefer the closed way: the aim is that no air enters the subdural space.…”
Section: Description Of the Techniquementioning
confidence: 96%